Impact of subclinical hypothyroidism on iron status and hematological parameters - Chandel, Rittu Surjit; Chatterjee, Gangadhar; Abichandani, Leela (Annals of Pathology and Laboratory Medicine, 2015)
Background: Thyroid hormones play an important physiological role to maintain balance of metabolism of entire human body. Erythrocyte abnormalities are frequently associated with thyroid disorder. Subclinical hypothyroidism, often a hidden condition, is associated with iron-deficiency anemia along with other disorders.Â  Thyroid hormones have a crucial role in metabolism and proliferation of blood cells. Thyroid dysfunction induces different effects on blood cells such as anemia, alters RBC indices including MCV and MCHC. In this study it was attempted to evaluate effect of subclinical hypothyroidism on hematological parameters and body iron store Methods: This retrospective study included 158 subjects, among which 118 were newly diagnosed, untreated subclinical hypothyroid [n=118], and 40 healthy euthyroid [n=40] individuals. The hematological parameters and thyroid profile of the subjects were assessed by the mean, standard deviation [SD]. Studentâ€™s t-test was used to report our results, with p-value < 0.05 considered as statistically significant. Results: In this study we have compared hemoglobin level, red cell indices, serum Ferritin among study group and euthyroid healthy group and found that mean hemoglobin, serum ferritin and RBC indices were significantly depleted in subclinical hypothyroid patient in comparison to euthyroid group. 21 of total 118 [17.8%] newly diagnosed subclinical hypothyroid patients was suffering from Iron deficiency anemia with hemoglobin level less than 10 g%. Conclusion: Subclinical hypothyroidism is often associated with anemia, depleted body iron store and complication of getting converted into primary hypothyroidism. As there is no significant clinical manifestation of SCH at earlier stages with anemia it is advisable to routinely investigate it for early detection allowing its early management.